Digital clones of the deceased in mental health care: Promises and perils - Masaki Iwasaki (Digital Health)
This letter highlights the emerging practice of employing digital clones of deceased individuals in grief care, addressing both their potential therapeutic benefits and the ethical and legal complexities they raise. While such technologies may offer novel avenues for bereavement support, there is a potential need for robust posthumous consent mechanisms and regulatory oversight to ensure respect for dignity and privacy.